The Use of Idioms in Advertisements (Journal of the College of Languages (JCL), 2014)
The power of advertising is immense. Producers of commercial goods and services routinely pour vast sums into promoting their wares through the advertising media, knowing that a successful campaign can win them vital market share , and that failure to advertise effectively can have devastating results . The function of advertising is promotional ; to draw our attention. In order to achieve this function it must reach its target audience , then capture that audience with a message that is both attractive and memorable. From a linguistic point of view, the language of advertising must be informative, instructive , distinctive and persuasive . It must employ a style of language that will help in attracting people`s attention and at the same time passing the information across . One of the linguistic devices used in advertising is the use of idioms. Idioms are used in advertisements because they are familiar to most potential customers in a society , where an element of an idiom is slightly changed or replaced by another word to create a pun and consequently a connection with a product. Idioms are frequently used in commercial advertisements as a rhetorical device to promote a given product by creating humor, attracting the reader`s attention and adding persuasive force to the message . They also reflect the cultural preferences and traditions of the country, therefore they can be fruitfully used for pedagogic purposes to raise awareness of the specific linguistic and cultural features of the foreign language. The research discusses the use of idioms in advertisements by analyzing examples chosen randomly from the advertisements websites.It also discusses the concept of advertisements , the language of advertising and the use if idioms in advertisements.